Legal and institutional frameworks for managing forest resources: a comparative study of ASEAN countries - Satria, Rahmad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This article examines the legal and institutional frameworks for managing forest resources across ASEAN countries through a comprehensive literature review methodology. With the increasing pressures of deforestation, climate change, and biodiversity loss, effective forest management has become a critical concern for sustainable development in the region. The study highlights the similarities and differences in legal structures, policies, and institutional arrangements among ASEAN member states, elucidating how these frameworks influence forest conservation and management practices. By analyzing existing research, reports, and legal documents, this study identifies best practices and challenges faced by each country in implementing effective forest governance. Key findings reveal that while some ASEAN countries have established robust legal frameworks and institutional capacities, others struggle with enforcement and coordination among stakeholders. The article emphasizes the importance of regional cooperation and harmonization of policies to enhance forest resource management across the ASEAN bloc. Additionally, it discusses the role of community involvement and indigenous rights in shaping sustainable forest governance. The insights gained from this comparative analysis provide valuable recommendations for policymakers and stakeholders aiming to improve forest management practices in the region, ultimately contributing to the sustainable use of forest resources and the achievement of environmental goals.